A Systematic Review of Digital Financial Application Reuse Intentions - Suci Alifah Rahmandani; Abror Abror; Zul Afdal (Faculty of Economics and Business Universitas Jenderal Soedirman, 2024)
This Systematic Literature Review examines the development of research on technology adoption and continuance intention in the context of digital financial services by reviewing 48 articles obtained from the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) screening process, using the Theory-Context-Method (TCM) framework, citation analysis, and keyword mapping with VOSviewer. The findings indicate that the Technology Acceptance Model (TAM) and Expectation Confirmation Theory (ECT/ECM) are the most frequently applied theoretical foundations, followed by UTAUT/UTAUT2, the Information Systems (IS) Success Model, and the Theory of Consumption Values ​​(TCV). Geographically, previous studies are predominantly located in Asia, with research contexts focused on digital financial applications. To obtain research results, PLS-SEM has been widely used as an analytical technique in previous studies. In addition to interpreting the results using PRISMA, an analysis using VOSviewer was also conducted, identifying continuance intention, trust, technology adoption, TAM, mobile banking, perceived ease of use, behavioral intention, fintech, and digital payments as interrelated bases. This review explains that continuance intention is a post-adoption behavior shaped by technological, psychological, social, and contextual factors.